A Gate Driver Based on Variable Voltage and Resistance for Suppressing Overcurrent and Overvoltage of SiC MOSFETs - Jiangui Chen; Yan Li; Mei Liang (Energies, 2019)
A SiC MOSFET is a suitable replacement for a Si MOSFET due to its lower on-state resistance, faster switching speed, and higher breakdown voltage. However, due to the parasitic parameters and the low damping in the circuit, the turn-on overcurrent and turn-off overvoltage of a SiC MOSFET become more severe as the switching speed increases. These effects limit higher frequency applications of SiC MOSFET. Based on the causes of overcurrent and overvoltage of SiC MOSFET, a novel gate driver with the variable driving voltage and variable gate resistance is proposed in this paper to suppress the overcurrent and overvoltage of SiC MOSFETs. The proposed gate driver can realize the variation in driving voltage and gate resistance during switching transitions. It not only suppresses the overcurrent and overvoltage of SiC MOSFETs, but also has little effect on switching loss. The working principle of the proposed gate driver is analyzed in this paper. Finally, experimental verification on a double-pulse test platform is performed to verify the effectiveness of the proposed gate driver.